The Effects of Suspended Solids on Oreochromis niloticus Filter Feeding Selection Mechanism and Ingestion of Microcystis aeruginosa - Robert , Olendi, (African Journal of Education,Science and Technology (AJEST), 2017)
Oreochromis niloticus species are filter feeder having gill raker on the bronchial arch modified to selectively sieve suspended solids into the alimentary canal. They have pharyngeal teeth for breaking algae cells and produce gastric acid that lyses blue-green algae in the stomach. Silt particles obtained from the bottom mud collected from Airthrey Loch (Lake) were passed through a series of sieves down to 63μm were used and sand particles used were also sieved through a series of sieves down to 68μm. O. niloticus fed on micro-pelleted diet of mean weight of 7.50 mg reared in re-cycled water system maintained at 270C were put into aerated three 5 litre experimental tanks with two replicates and control. Concentrations of 50 and 150mg/l of sand and algae and the same for silt and algae were introduced in the tanks to which 50 and 150mg/l dry weight of algae were added respectively. Experimental fish were left for 8 hours then removed and killed by piercing using a scalpel at the back of the brain at intervals of 15, 30, 45, and 60 minutes after feeding. The gill arches were carefully removed and put into a Petri-dish and particles observed under dissecting microscope. The stomach and gut contents were removed by micro-pipette and put on a microscope slide and examined under microscope. In this study, it was found that silt particles were entangled and bound in the copious mucus of the gill structures but not algae and sand particles. The stomach and gut contents had algae and silt particles which proved difficult to quantify because the remnants of ingested particles invariably included both detritus material. Sand particles were not seen in the entire gill apparatus stomach and gut. Thus it can be concluded that silt and algae particles are ingested but not sand particles.